Quality of Life with Disabilities: Insights into Residential Institutions in Greenland - Rubin, Sofie; Nørtoft, Kamilla (Études Inuit Studies, 2023)
This paper explores how values for quality of life are being expressed and practiced in residential institutions for people with disabilities in Greenland and how this corresponds with and reflects peqqinneq and its key values of balance, acceptance, and harmony. In this study, peqqinneq encompasses a holistic understanding of what quality of life constitutes for the residents. Data was generated through qualitative interviews with 29 managers and employees and 16 residents from 8 residential institutions and is supplemented with observational data from 7 residential institutions. Our analysis focuses mainly on informants’ perceptions of quality of life, meaningful activities, and social relations, including the role of relatives.